Approximation Solution of Fredholm Integral Equation Using Adomian Decomposition Method (Journal of Madenat Alelem, 2010)
In this paper, Adomian Decomposition method has been used to find the approximation solution for the linear Fredholm integral equation of the second kind. In this method the solution of a functional equation is considered as the sum of an infinite series usually converging to the solution, and the Adomian decomposition method is also used to solve linear integral equation. Finally, numerical example are prepared to illustrate these considerations.